IMPLEMENTASI MESIN HIDROTERMAL UNTUK PENGOLAHAN LIMBAH POPOK BAYI - Esta Larosa; Abdi Gunawan Djafar; Niniek Pratiwi; Syafriyani; Sartika Dewi Usman; Sri Ayu Ashari (Jurnal Pendidikan Teknik Mesin, 2024)
The use of disposable baby diapers continues to increase in line with population growth and lifestyle changes that prioritize convenience. However, baby diaper waste has become a significant environmental issue due to its synthetic and chemical components that are difficult to decompose naturally. This study aims to apply hydrothermal machine technology as an environmentally friendly and efficient solution for processing baby diaper waste. Hydrothermal technology utilizes high temperatures and pressure to decompose organic and synthetic materials in diapers, resulting in reusable products such as construction materials, alternative energy, or fertilizers. The study results show that the hydrothermal process can reduce diaper waste volume by up to 90% and produce valuable materials. The implementation of this technology supports waste reduction at landfills (TPA) and advances the vision of zero waste, making it a sustainable solution for waste management challenges.